Targeting Phosphorylation of p21-activated Kinase 1 at Thr423 Induces Cell Cycle Arrest and Apoptosis in Cutaneous T-cell Lymphoma Cells - Yimeng Wang; Weiwei Li; Qian Zhang; Xiaoguang Gu; Xinglan He; Yuehua Men; Chunlei Zhang (Medical Journals Sweden, 2019)
Cutaneous T-cell lymphoma (CTCL) represents a rare group of extranodal T-cell lymphoproliferative diseases. Due to poor clinical outcome of CTCL, there is an urgent need for new and improved therapies. A small molecule, IPA-3, which inhibits p21-activated kinase 1 (PAK1), has shown therapeutic potential in various types of malignancies. In the present study, the anti-tumor effect of IPA-3 and its underlying molecular mechanism was evaluated. High expression of phosphorylated-PAK1 (pho-PAK1) was seen in CTCL lesional skin compared to benign inflammatory dermatoses. IPA-3 could significantly inhibit the proliferation of 3 CTCL lines in a dose- and time-dependent manner. The percentage of apoptotic cells was higher in the treatment group. Further, IPA-3 treatment caused increased EGR1 protein levels and decreased apoptosis-related BCL-2 and pho-BAD protein levels. In summary, inhibition of pho-PAK1 has significant anti-tumor effects in CTCL cells and it can be explored as a future therapeutic option.